209k views
1 vote
Someone help me I will mark you as brain

Someone help me I will mark you as brain-example-1

2 Answers

3 votes

Answer:

-1

Explanation:

h(x) = -3x - 10

h(-3) means to replace the x in the problem with the value of -3 and

solve.

h(-3) = -3(-3) - 10

h(-3) = 9 - 10

h(3) = -1

User GuyH
by
5.1k points
3 votes

Explanation:

that is really, really simple.

h(-3) means that we put the argument (-3) into the formula of the function everywhere where there is x.

h(x) = -3x - 10

so,

h(-3) = -3×-3 - 10 = 9 - 10 = -1

User JPR
by
5.2k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.